2010
DOI: 10.11646/zootaxa.2445.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Two new Stephanostomum-like cercariae (Digenea: Acanthocolpidae) from Nassarius dorsatus and N. olivaceus (Gastropoda: Nassariidae) in Central Queensland, Australia

Abstract: Two newStephanostomum-like cercariae, Cercaria capricornia VII and Cercaria capricornia VIII (Digenea: Acanthocolpidae), are described from the nassariid gastropods Nassarius dorsatus and Nassarius olivaceus collected from the intertidal zone in the Capricornia region of Central Queensland, Australia. Morphological analysis of these new cercariae was augmented with DNA sequence data from the large subunit (LSU) ribosomal DNA region to aid in identification. Bayesian inference analysis of the LSU rDNA revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We believe that Stephanostomum's positive response to fishing may arise from a trophic cascade in which fish that prey on snails are lost to fishing (as in McClanahan, 1989), leading to an increase in the snail intermediate host of Stephanostomum (Wood, Sandin, et al, 2014 Barnett, Miller, and Cribb (2010)], which are prey for large, molluscivorous fishes (Palmer, 1979;Vermeij, 1977). Possessing first intermediate hosts that benefit from fishing might predispose Stephanostomum spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that Stephanostomum's positive response to fishing may arise from a trophic cascade in which fish that prey on snails are lost to fishing (as in McClanahan, 1989), leading to an increase in the snail intermediate host of Stephanostomum (Wood, Sandin, et al, 2014 Barnett, Miller, and Cribb (2010)], which are prey for large, molluscivorous fishes (Palmer, 1979;Vermeij, 1977). Possessing first intermediate hosts that benefit from fishing might predispose Stephanostomum spp.…”
Section: Resultsmentioning
confidence: 99%
“…metacercariae we detected are unknown, other Stephanostomum spp. are known to use large, sand‐ and mud‐dwelling whelks (superfamily Buccinoidea) and moon snails [superfamily Naticoidea; see table 4 in Barnett, Miller, and Cribb ()], which are prey for large, molluscivorous fishes (Palmer, ; Vermeij, ). Possessing first intermediate hosts that benefit from fishing might predispose Stephanostomum spp.…”
Section: Discussionmentioning
confidence: 99%
“…Køie 51 first described the presence of Opechona sp. cercariae in Nassarius pygmaeus from Scandinavia, Barnett et al 60 reported the presence of Stephanostomum -like cercariae from Australian Nassaridae. Lepocreadiid digenean probably belonging to Opechona sp.…”
Section: Discussionmentioning
confidence: 99%
“…and Cryptogonimidae gen. sp. (Table 2), it is likely that gastropods act as first intermediate hosts [60–62]. Predatory fishes such as serranids, lutjanids or carangids (among others) could be the definitive hosts of these digeneans (see checklist 1 in [63]).…”
Section: Discussionmentioning
confidence: 99%